Protectin DX increases survival in a mouse model of sepsis by ameliorating inflammation and modulating macrophage phenotype - Haifa Xia (Nature Portfolio, 2017)
Abstract Recently, a serial of studies have demonstrated that lipid mediators derived from Omega-3 fatty acid docosahexaenoic acid have pro-resolving or anti-inflammatory effects in many inflammatory diseases. Here, we sought to evaluate whether Protectin DX (PDX, an isomer of Protecin D1), a newly identified lipid mediator, could protect mice against sepsis and explore the underling mechanism. Animal model of sepsis was established by cecum ligation and puncture (CLP). We found that PDX increased overall survival rate within eight days and attenuated multiple organ injury in septic mice. In addition, PDX reduced pro-inflammatory cytokines and bacterial load 24 h after CLP. Moreover, PDX promoted phagocytosis of peritoneal macrophages and increased the percentage of M2 macrophages in peritoneum of septic mice. In vitro, M2 macrophage markers (Arg1 and Ym1) and its transcriptional regulator (peroxisome proliferator-activated receptor-γ, PPAR-γ) were upregulated in Raw264.7 macrophages challenged with PDX. GW9662 (a PPAR-γ inhibitor) and PPAR-γ siRNA abrogated the induction of Arg1 and Ym1 by PDX in Raw264.7 cells. Taken together, our results suggest that PDX is able to promote M2 polarization, enhance phagocytosis activity of macrophage and accelerate resolution of inflammation, finally leading to increased survival rate of septic mice.